Forward masking in the superior paraolivary nucleus of the rat - Gao, Fei; Kadner, Alexandra; Felix, Richard A.; Chen, Liang; Berrebi, Albert S. (Brain Structure and Function, 2017)
In natural acoustic environments, perception of acoustic stimuli depends on the recent contextual history. Forward masking describes a phenomenon whereby the detection threshold of a probe stimulus is markedly increased when it is preceded by a masking stimulus. The aim of this study was to characterize the offset response of single units in the superior paraolivary nucleus (SPON) to a forward masking paradigm. We observed two distinct response types to forward-masked stimuli, namely inhibited and facilitated responses. In the presence of a default masking stimulus, inhibited responses to probe stimuli were characterized by elevated thresholds and/or diminished spike counts, whereas facilitated responses were characterized by reduced thresholds and increased spike counts. In units with inhibited responses to the probe stimuli, probe thresholds increased and spike counts decreased as masker intensity was raised or the masker-to-probe delay was shortened. Conversely, in units with facilitated responses to the probe stimuli, probe thresholds decreased and spike counts increased as masker intensity was raised or the masker-to-probe delay was shortened. Neither inhibited nor facilitated responses to the forward masking paradigm were significantly dependent on masker frequency. These findings suggest that SPON responses are not themselves consistently subject to the same forward masking properties observed in other nuclei along the ascending auditory pathway. The potential neural mechanisms of the forward masking responses observed in the SPON are discussed.